Changes in whole metabolites after exenatide treatment in overweight/obese polycystic ovary syndrome patients. (10th July 2019) - Tang, Liang; Yuan, Lei; Yang, Gangyi; Wang, Feng; Fu, Mao; Chen, Min; Liu, Dongfang
Abstract: Objective: Exenatide is a new agent for diabetes therapy, and its use in polycystic ovary syndrome (PCOS) has gradually increased; however, the clinical benefit and metabolic improvement need further evidence. This research aimed to study the changes in whole metabolites before and after exenatide treatment in overweight/obese PCOS patients to gain a better understanding of exenatide for the treatment of PCOS. Methods: Sixty‐seven women, including 32 with PCOS and 35 age‐matched controls, were recruited. The metabolite changes were detected with nontargeted gas chromatography‐tandem mass spectrometry (NTGC‐MS) before and after exenatide treatment, and changes in clinical biochemical characteristics were also observed. Results: A total of 62 metabolites were differentially expressed between the healthy and PCOS groups, and 31 differentially expressed metabolites were detected before and after exenatide treatment. Abnormal lipid metabolism and amino acid metabolism were the main metabolic disorders. Exenatide improved lipid and amino acid metabolism, especially amino acid metabolites. Three types of branched‐chain amino acids (valine, leucine and isoleucine), two types of aromatic amino acids (phenylalanine and tyrosine) and lysine are important potential metabolites for the therapeutic efficacy of exenatide. Many abnormal metabolic disorders are related to insulin resistance, oxidative stress and even ovulatory dysfunction. Moreover, in this small sample clinical study, we also found that exenatide improved insulin sensitivity, reduced body weight and improved glycolipid metabolism in PCOS. Conclusions: NTGC‐MS‐based metabolic pathway analysis revealed that exenatide has a beneficial effect on overweight/obese PCOS patients by regulating metabolic disorders, especially amino acid disorders.